PEMANFAATAN MEDIA FLASH CARD UNTUK MENINGKATKAN KEMAMPUAN MEMBACA HURUF HIJAIYAH (Penelitian pada Siswa Kelas Satu Sekolah Dasar Tempurejo I, Kabupaten Magelang) - Khusnul Laely, Khadziq Ma’arif (Universitas PGRI Yogyakarta, 2017)
This study aims to determine the increase in the ability to read letters hijaiyah Elementary School first grade through the use of flash media card in the SD TempurejoI Magelang regency. Research carried out by the draft Action Research (PTK) with twocycles, each of which includes planning, implementation, observation, and reflection.The subject of research as many as twenty students in the first grade, elementaryTempurejo I Academic Year 2015/2016. Methods of data collection using observation,testing, and documentation. Data analysis methods used by quantitative descriptiveanalysis to determine the increase in the ability to read letters hijaiyah ElementarySchool first grade through the use of flash media cards. Based on the research results,the ability to read letters hijaiyah increased with the results of the initial ability to readletters ability hijaiyah reached 25.7%, the first cycle reaches 54.29% and cycle IIreached 88.57%. This means that the use of flash media cards can improve the ability toread letters hijaiyah Elementary School first-grader.Keywords: Media flash cards, reading, letter hijaiyah childÂ